N-Acetyl Cysteine-Cadmium Telluride NAC-CdTe QDs for Detecting the Damaged DNA in Cancerous Diseases - Fadhil, Eman A.A.; Abdullah, Manal M.; Lafta, Fadhel M. (Iraqi Journal of Science, 2024)
In this study water-soluble N-Acetyl Cysteine Capped-Cadmium Telluride QDs (NAC/CdTe nanocrystals) using N-acetyl cysteine as a stabilizer were prepared to investigate the utility of quantum dots (QDs) in distinguishing damaged DNA, (extracted from blood samples of leukaemia patients), from intact DNA (extracted from blood samples of healthy individuals) to be used for biosensing application. Based on the optical characterization of the prepared QDs, the XRD results revealed the formation of the NAC-CdTe-QDs with a grain size of 7.1nm. Whereas, the SEM test showed that the spherical size of the NAC-CdTe-QDs lies within 11~33nm. NAC-CdTe-QDs have superior PL emission properties at of 550nm and UV-Vis absorption peak at 300nm. The energy gap measurement through PL and UV–Vis was found to be 2.2eV and 2.3 eV, respectively. The interaction between the synthesized QDs and the extracted genomic DNA (both cancer damaged DNA and healthy undamaged DNA) was analysed optically, and compared to the normal reference DNA. The results showed a shift in the maximum fluorescence emission intensities (observed at 540nm nm for a damaged sample and 535 for a reference cell). Based on the obtained fluorescence results, the present study reached the conclusion that the prepared core/shell QDs could be employed as probes for diagnosing genetically disrupted DNA that is associated with malignant diseases from healthy DNA.